The general public knowledge, attitude, and practices regarding COVID-19 during the lockdown in Asian developing countries - Sikandar Ali, Qalati; Dragana, Ostic; Mingyue, Fan; Ahmed, Sarfaraz; Galván Vela, Esthela; Zufar, Zuhaib; Muhammmad Suho, Jan (My University, 2021)
The recent outbreak of coronavirus disease (COVID-19) is the worst global crisis. Since no successful treatment and vaccine have been reported, efforts to improve the public’s knowledge, attitudes, and practices are critical to reducing the spread of COVID-19. This study aims to investigate the general public knowledge, attitude, and practices regarding COVID-19. A cross-sectional online survey was conducted in three developing countries (China, India, and Pakistan). The reason for choosing only three countries is to identify the cross-border effect statistically and data collection constraints. The IBM SPSS version 23.0 was used for descriptive, univariate, and multivariate analysis of the study. One thousand one hundred and sixty participants completed the study, one-quarter of them were female, and three-quarters were male. The study’s findings evidenced that the knowledge and attitude correlation was 58.4% and between knowledge and practices 18.2%. Furthermore, the knowledge was found lower in females, among India and Pakistan, and people aged less and equivalent to 30 years. The attitudes among respondents were found poorer among unmarried females and India and Pakistan residents. While the practices found lower among employed, unemployed and, respondents had a bachelor’s degree, and females reside in India. And future studies should focus on factors that influence the government regarding the imposition of lockdown, boost the economy in the pandemic, and motivate the general public to follow the health institution’s instructions.
SAGE Journals
Keywords: Knowledge; Attitudes; Practices; Developing countries; General public; Lockdown; COVID-19; Campus Tijuana